Status Quo of Professional–Patient Relations in the Internet Era: Bibliometric and Co-Word Analyses - Wang, Zekun; Deng, Zhaohua; Wu, Xiang (International journal of environmental research and public health, 2019)
Background: Incidents of violence against medical staff have increased in intensity, showing the deteriorating relationship between doctors and patients in China over the past few years. In addition, professional–patient relations have been significantly affected in the Internet era in China, which has attracted great attention from many scholars. This study aims to analyze the research status of professional–patient relations in the Internet era in China and further reveal its research pattern and trends. Methods: This study collected journal articles published during the past 21 years from the Wanfang Data Knowledge Service Platform. Then, bibliometric analysis was carried out, including publication growth, core author and collaborative degree, highly cited papers, journal distribution, and institution distribution analyses. We also analyzed the subject heading–source literature matrix and co-occurrence matrix of keywords through hierarchical cluster, social network, and strategic diagram analyses. Results: The number of articles has continually risen since 1998, which follows the growth law of literature. Furthermore, the distribution of these studies obeys Bradford’s law of scattering, and mainly concentrates on the fields of medicine and health technology. The distribution of high-frequency keywords follows Zipf’s law. Conclusions: We identified eight focal research directions, namely: website building (especially for professional–patient interaction), telemedicine, professional–patient communication and network public opinion, professional–patient contradiction and health education, new media, follow-up interaction platform, healthcare reform and computer network, and medical ethics.